Electrochemical Actuators: Heterogeneous Conductance‐Based Locally Shape‐Morphable Soft Electrothermal Actuator (Adv. Mater. Technol. 2/2020). Issue 2 (10th February 2020) - Ahn, Junseong; Jeong, Yongrok; Zhao, Zhi‐Jun; Hwang, Soonhyoung; Kim, Kyuyoung; Ko, Jiwoo; Jeon, Sohee; Park, Jaeho; Kang, Hyeokjung; Jeong, Jun‐Ho; Park, Inkyu
Abstract : In article number 1900997, Jun‐Ho Jeong, Inkyu Park and co‐workers introduce a novel method of electrothermal actuator (ETA) design, revealing that heterogeneous conductance control of ETA realizes locally shape‐morphable actuation. The proposed actuator can be applied to soft robotics for handling various objects in diverse actuation shapes.